ANALISIS IMBANGAN AIR PADA DAERAH IRIGASI BRAJAN KABUPATEN KARANGANYAR - Putra, Angga Andreansah; Wijayanti, Paska; Nursetyo, Gatot (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
Brajan Dam is one of the dams in Karanganyar Regency. Brajan Dam has an irrigation area of 137 ha which is managed by the Gandul area. As time goes by, it is necessary to refresh appropriate planting patterns so that water needs can be met. This research aims to determine the water balance in the Brajan Irrigation Area. The method used is a quantitative descriptive method and direct observation. The analysis stage begins with exploring the irrigation network and then collecting secondary data at the research location. The secondary data was obtained from the Bengawan Solo Water Resources Development Center (BPSDA). The analysis stage is by comparing the need and availability of irrigation water. Based on the results of the analysis in the Brajan irrigation area, it was found that the annual average availability of irrigation water was 0.32 m3/second. For the maximum water requirement for Brajan irrigation, the results were 0.37 m3/second in the first month of July during the second rice planting period. For the Brajan irrigation balance, results were obtained with a water shortage value of 17% and adequate water requirements of 83%. Thus, the availability of water in the Brajan irrigation area is still sufficient to meet agricultural irrigation needs.